Key Modulatory Role of Presynaptic Adenosine A2A Receptors in Cortical Neurotransmission to the Striatal Direct Pathway - César Quiroz; Rafael Luján; Motokazu Uchigashima; Ana Patrícia Simoes; Talia N. Lerner; Janusz Borycz; Anil Kachroo; Paula M. Canas; Marco Orru; Michael A. Schwarzschild; Diane L. Rosin; Anatol C. Kreitzer; et al. (The Scientific World Journal)
Basal ganglia processing results from a balanced activation of direct and indirect striatal efferent pathways, which are controlled by dopamine D1 and D2 receptors, respectively. Adenosine A2A receptors are considered novel antiparkinsonian targets, based on their selective postsynaptic localization in the indirect pathway, where they modulate D2 receptor function. The present study provides evidence for the existence of an additional, functionally significant, segregation of A2A receptors at the presynaptic level. Using integrated anatomical, electrophysiological, and biochemical approaches, we demonstrate that presynaptic A2A receptors are preferentially localized in cortical glutamatergic terminals that contact striatal neurons of the direct pathway, where they exert a selective modulation of corticostriatal neurotransmission. Presynaptic striatal A2A receptors could provide a new target for the treatment of neuropsychiatric disorders.